2008
DOI: 10.1159/000112599
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Models for Prognostic Prediction in Patients with Renal Cell Carcinoma

Abstract: Objectives: The objectives of this study are to catalogue all models developed to predict survival of RCC patients and to identify the ones to be used in different situations. Methods: A systematic review was performed searching with a free text and MeSH strategy 3 electronic databases. For each model, the following parameters were identified: number, features of the patients; evaluation endpoints; clinical and/or pathological variables included; concordance indexes (cI). Results: The research retrieved 156 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 73 publications
0
23
0
Order By: Relevance
“…This aim was achieved for the whole range of tumor sizes by using readily available parameters such as the ASA score and patient age. Both parameters, although seemingly not directly related to metastatic potential, have been shown to be useful as both patient age and performance, which is related to comorbidity, have been shown to be predictive factors for survival in RCC disease [16,17,18,19,20,21,22,23]. As our database does not include a performance score for all patients, we used the ASA score as an index of comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…This aim was achieved for the whole range of tumor sizes by using readily available parameters such as the ASA score and patient age. Both parameters, although seemingly not directly related to metastatic potential, have been shown to be useful as both patient age and performance, which is related to comorbidity, have been shown to be predictive factors for survival in RCC disease [16,17,18,19,20,21,22,23]. As our database does not include a performance score for all patients, we used the ASA score as an index of comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…In as many as 95% of autopsies metastatic lesions have been found, the most commonly expected sites being the lung, liver, bone and brain. Patients with metastatic RCC have a poor prognosis with an estimated 5-year survival rate of ^ 10% [3][4][5][6] . Secondary neoplasms to the prostate gland are in general a rare event, leukemia and non-Hodgkin's lymphoma being the main primary malignancies [1] .…”
Section: Discussionmentioning
confidence: 99%
“…A phase III study demonstrated a median 6-month extended progression-free survival interval with sunitinib (11 months) than with IFN-␣ (5 months) [5] . Prior to the era of targeted therapies, multiple surgical resections, radiofrequency ablations or cytokine therapy were standard treatment options resulting in long-term survival in selected patients only [6] . Prediction of survival of metastatic renal cell carcinoma patients can be calculated with the Leibovitch or Motzer algorithms [7] .…”
mentioning
confidence: 99%